Injection molding parameter optimization using the Taguchi method for highest green strength for bimodal powder mixture with SS316L in PEG and PMMA - Jamaludina, K. R.; Muhamad, N.; Ab. Rahman, M. N.; Amin, S. Y. M.; Murtadhahadi, I; Ismail, M. H. (Metal Powder Industries Federation, 2008)
Injection molding parameters for the highest green strength of the metal powder mixture has been optimized using L27 (313) Taguchi orthogonal array. Parameters optimized are the injection pressure, injection temperature, powder loading, mold temperature, holding pressure and injection rate. The metal powder mixture used is SS316L powder in bimodal particle-sized distribution, and a composite binder consisting of PEG and PMMA. Stearic acid is used as a surfactant to improve its flowablity. Interactions of the injection pressure, injection temperature and powder loading were studied. Analysis of variance (ANOVA) for the best signal to noise ratio (S/N) presents the contribution of the parameters to the quality characteristic (green strength). Results show that the mold temperature contributes about 48.28 % (highest) followed by the powder loading (8.33 %) and, injection rate (6.00 %) while, other parameters were pooled because the confident level was lower than 90 %. Nevertheless, the analysis of variance does not show any contribution from the interactions.